Implementasi Kurikulum Spiritual Terhadap Pertumbuhan Spiritual Siswa di SMK Kristen Terang Bangsa di Kota Semarang - Widyasih Susan Maryastuti; Luki Krispriyanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The spiritual curriculum must be structured as well as possible so that it can fulfill every need that students need to support their spiritual growth so that students can grow more mature in accordance with biblical teachings.The purpose of this research is to find out whether the implementation of the spiritual curriculum applied in class devotion, level devotion, and YouthinC2 affects the spiritual / character growth of students at SMK Kristen Terang Bangsa so that it can find the right implementation for the right curriculum that can be applied, it is hoped that there will be adjustments to the implementation of the spiritual curriculum at SMK Kristen Terang Bangsa. The population in this study were students of SMK Kristen Terang Bangsa in grades XI, XII, and alumni along with class pastors and teachers for the 2023-2024 school year and the 2024-2025 school year. Implementing the spiritual curriculum applied in class devotion, level devotion, and YouthinC2 has a positive effect on the spiritual growth/ character of Terang Bangsa school students.